A kind of ferromanganese phosphate precursor and preparation method thereof
By introducing UiO-66-NH2/Nb2CTx composite material and surfactant in the preparation of ferromanganese phosphate precursors, combined with the formation of zirconium-doped carbon layer, the poor circulation performance and specific capacity of lithium manganese phosphate positive electrode material are solved. Problem, high capacity and good circulation performance lithium batteries are achieved.
Patent Information
- Application Number
- CN202411756168.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The lithium manganese phosphate positive electrode material finally prepared by the existing ferromanganese phosphate precursor has problems of poor circulation performance and poor specific capacity.
By using phosphoric acid solution, iron powder, manganese carbonate, surfactant and UiO-66-NH2/Nb2CTx composite materials, the precursor of manganese phosphate is prepared through chemical reactions and solid phase reactions, and the iron, manganese, and phosphorus are accurately controlled. The molar ratio is formed and a zirconium doped carbon layer is formed during the calcination process to build an efficient conduction network.
The prepared lithium iron manganese phosphate cathode material has a large contact area and high ion and electron transport performance, which improves the capacity and cycling performance of lithium batteries.
Smart Images

Figure CN119218995B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a ferromanganese phosphate precursor and a preparation method thereof. Background Art
[0002] At present, due to the low working voltage (3.4V) of lithium iron phosphate, the actual energy density is low and it can no longer meet the growing demand for high energy density in electric vehicles and hybrid electric vehicles. 4 It has begun to receive more and more attention because it has a higher working potential (4.1V) and a similar crystal structure and theoretical capacity (171mAh / g) to lithium iron phosphate. 4 The energy density can be increased by about 20%.
[0003] Since LiMnPO 4 The low conductivity of LiMnPO leads to low lithium ion diffusion rate, which greatly limits the 4 The capacity of LiMnPO 4 It can only provide a capacity of less than 120 mAh / g. In order to solve the above problems, replacing part of Mn with Fe has been proven to effectively improve the capacity of LiMnPO 4 Conductive properties and high voltage potential, therefore, LiMn 1-X Fe x PO 4 (0<x<1) materials have become a hot topic in current research. Among them, ferromanganese phosphate precursors have also received increasing attention.
[0004] The preparation method of ferromanganese phosphate precursor is similar to that of iron phosphate, mainly including hydrothermal method, coprecipitation method, high temperature solid phase reaction method, etc. However, the lithium ferromanganese phosphate positive electrode material finally prepared by obtaining the ferromanganese phosphate precursor by the above method still has the problems of poor cycle performance and poor specific capacity. Summary of the invention
[0005] The purpose of the present invention is to provide a ferromanganese phosphate precursor and a preparation method thereof, aiming to solve the problem that the lithium ferromanganese phosphate positive electrode material finally prepared from the existing ferromanganese phosphate precursor still has poor cycle performance and poor specific capacity.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A manganese ferrophosphate precursor, comprising phosphoric acid solution, iron powder, manganese carbonate, surfactant and UiO-66-NH 2 / Nb 2 CT x Composite materials are prepared through chemical reactions and solid phase reactions.
[0008] Furthermore, the UiO-66-NH 2 / Nb 2 CT x The method for preparing the composite material comprises the following steps:
[0009] Zirconium chloride and 2-aminoterephthalic acid were added to DMF and stirred until completely dissolved to obtain a mixed solution a. 2 CT x The mixture a was added to the reactor, and the reaction was carried out at 120°C for 24 h under vacuum conditions. After the reaction was completed, the mixture was cooled to room temperature. The reaction product was washed with DMF and anhydrous ethanol for 3-5 times respectively, and freeze-dried to obtain UiO-66-NH 2 / Nb 2 CT x Composite materials.
[0010] Further, zirconium chloride, 2-aminoterephthalic acid, DMF and Nb 2 CT x The dosage ratio is 400mg:248mg:30mL:1.5-3g, and the solvent thermal method is used to prepare Nb 2 CT x Introducing UiO-66-NH 2 , Preparation of UiO-66-NH 2 / Nb 2 CT x Composite materials.
[0011] Furthermore, the Nb 2 CT x The preparation method comprises the following steps:
[0012] Add lithium fluoride to the hydrochloric acid solution, stir for 3-5 minutes, then add Nb 2 AlC, keep warm at 40-50℃ for 24h. After the reaction, wash with dilute hydrochloric acid and ultrapure water for 2-3 times (the speed of the centrifuge is 3000-4000rmp, and the time is 5-8min). After washing, collect the precipitate, and vacuum dry the precipitate to obtain Nb 2 CT x .
[0013] Further, lithium fluoride, hydrochloric acid solution and Nb 2 The dosage ratio of AlC is 1.6g:25-30mL:1g, and the concentration of hydrochloric acid solution is 9mol / L.
[0014] Furthermore, Nb 2 The average particle size of AlC is 0.5-50um.
[0015] Furthermore, the concentration of the dilute hydrochloric acid is 1-2 mol / L.
[0016] The method for preparing the above-mentioned ferromanganese phosphate precursor comprises the following steps:
[0017] S1, adding iron powder to phosphoric acid solution, stirring and reacting at 40-80° C. for 3-5 hours to obtain a first reaction mixture;
[0018] S2, manganese carbonate, surfactant and UiO-66-NH 2 / Nb 2 CT x The composite material is added to the first reaction mixture, and stirred for reaction at 40-80° C. for 2-4 hours to obtain a second reaction mixture;
[0019] S3. The second reaction mixture is filtered, the filter cake is washed with pure water for 3-5 times, dried and then calcined to obtain a manganese iron phosphate precursor.
[0020] Furthermore, the concentration of the phosphoric acid solution is 75-85 mol / L.
[0021] Furthermore, the molar ratio of manganese in manganese carbonate, iron in iron powder and phosphorus in phosphoric acid solution is 0.55-0.65:0.35-0.45:1-1.05, UiO-66-NH 2 / Nb 2 CT x The amount of the composite material is 0.5-2.0% of the total mass of manganese carbonate, iron powder and phosphoric acid, and the amount of the surfactant is 0.5-1% of the mass of manganese carbonate.
[0022] Furthermore, the surfactant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and citric acid mixed in any proportion.
[0023] Furthermore, the particle size of the iron powder is ≤100um.
[0024] Furthermore, the calcination temperature is 500-700°C and the calcination time is 5-8h.
[0025] Beneficial effects of the present invention:
[0026] The present invention provides a ferromanganese phosphate precursor and a preparation method thereof, wherein iron powder is used as an iron source, manganese carbonate is used as a manganese source, phosphoric acid is used as phosphoric acid, UiO-66-NH 2 / Nb 2 CT xThe composite material is used as the skeleton, the molar ratio of iron, manganese and phosphorus is precisely controlled, and the use of surfactants is used to obtain a manganese iron phosphate precursor with uniform particle size, good morphology and porous structure. The manganese iron phosphate lithium positive electrode material prepared in this way has a large contact area with the electrolyte and has high ion and electron transmission performance, ultimately making the prepared lithium battery have the characteristics of high capacity and good cycle performance.
[0027] Based on the excellent electronic conductivity and lithium ion transport mechanism of Mxenes materials, the present invention first obtains Nb 2 CT x Materials, then in Nb 2 CT x Surface introduction of UiO-66-NH 2 , UiO-66-NH 2 The introduction of Nb 2 CT x The dispersion of the material in the mixed solution, on the other hand, UiO-66-NH 2 The internal organic ligands are pyrolyzed into a carbon network skeleton during the calcination process, and combined with the participation of zirconium ions, a zirconium-doped carbon layer is formed, which is combined with Nb 2 CT x The materials together form a skeleton structure, building an efficient conduction network between the ferromanganese phosphate particles, ultimately improving the lithium ion diffusion rate and electronic conductivity of lithium iron manganese phosphate.
[0028] The present invention has come to the conclusion through multiple studies that the amount of UiO-66-NH2 / Nb2CTx composite material should be accurately controlled. The introduction of a small amount of UiO-66-NH2 / Nb2CTx composite material is not enough to build a relatively complete transmission network on the surface of lithium iron manganese phosphate, and it is difficult to effectively improve the electrochemical properties of lithium iron manganese phosphate. If an excessive amount of UiO-66-NH2 / Nb2CTx composite material is introduced, the UiO-66-NH2 / Nb2CTx composite material will be stacked together, hindering the transfer of lithium ions and weakening the electrochemical properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention will be further described below in conjunction with the accompanying drawings.
[0030] Figure 1 This is a SEM image of the lithium manganese iron phosphate positive electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0033] Preparation Example 1
[0034] UiO-66-NH 2 / Nb 2 CT x The method for preparing the composite material comprises the following steps:
[0035] 400 mg of zirconium chloride and 248 mg of 2-aminoterephthalic acid were added to 30 mL of DMF and stirred until completely dissolved to obtain a mixed solution a. 1.5 g of Nb 2 CT x The mixture a was added to the reactor and reacted at 120 °C for 24 h under vacuum. After the reaction was completed, it was cooled to room temperature. The reaction product was washed three times with DMF and anhydrous ethanol respectively, and freeze-dried to obtain UiO-66-NH 2 / Nb 2 CT x Composite materials.
[0036] Nb 2 CT x The preparation method comprises the following steps:
[0037] Add 16g lithium fluoride to 250mL 9mol / L hydrochloric acid solution, stir for 3min, then add 10g Nb 2 AlC, keep warm at 40℃ for 24h. After the reaction, wash twice with dilute hydrochloric acid and ultrapure water respectively (the speed of the centrifuge during washing is 3000rmp, and the time is 5min). After washing, collect the precipitate, and vacuum dry the precipitate to obtain Nb 2 CT x .
[0038] Among them, Nb 2 The average particle size of AlC is 0.5-50um, and the concentration of dilute hydrochloric acid is 1mol / L.
[0039] Preparation Example 2
[0040] UiO-66-NH 2 / Nb2 CT x The method for preparing the composite material comprises the following steps:
[0041] 400 mg of zirconium chloride and 248 mg of 2-aminoterephthalic acid were added to 30 mL of DMF and stirred until completely dissolved to obtain a mixed solution a. 3 g of Nb 2 CT x The mixture a was added to the reactor, and the reaction was carried out at 120 °C for 24 h under vacuum conditions. After the reaction was completed, the reaction product was cooled to room temperature, and the reaction product was washed with DMF and anhydrous ethanol for 5 times respectively, and freeze-dried to obtain UiO-66-NH 2 / Nb 2 CT x Composite materials.
[0042] Nb 2 CT x The preparation method comprises the following steps:
[0043] Add 16g lithium fluoride to 300mL 9mol / L hydrochloric acid solution, stir for 5min, then add 10g Nb 2 AlC, keep warm at 50℃ for 24h. After the reaction, wash with dilute hydrochloric acid and ultrapure water for 3 times (the speed of the centrifuge during washing is 4000rmp, and the time is 8min). After washing, collect the precipitate, and vacuum dry the precipitate to obtain Nb 2 CT x .
[0044] Among them, Nb 2 The average particle size of AlC is 0.5-50um, and the concentration of dilute hydrochloric acid is 2mol / L.
[0045] Comparative Example 1
[0046] UiO-66-NH 2 / Nb 2 CT x The method for preparing the composite material comprises the following steps:
[0047] 400 mg UiO-66-NH 2 and 1.5 g Nb 2 CT x Add to the mixer and stir at 500 rpm for 20 min to obtain UiO-66-NH 2 / Nb 2 CT x Composite materials, Nb 2 CT x The preparation process is the same as that of Preparation Example 1.
[0048] Example 1
[0049] A method for preparing a ferromanganese phosphate precursor comprises the following steps:
[0050] S1, adding 1.47 kg of iron powder (particle size ≤ 100 um) into 1 L of 75 mol / L phosphoric acid solution, stirring and reacting at 40° C. for 5 h to obtain a first reaction mixture;
[0051] S2, 4.7 kg manganese carbonate, 23.5 g sodium dodecylbenzene sulfonate and 67.6 g UiO-66-NH 2 / Nb 2 CT x The composite material is added to the first reaction mixture, and stirred for reaction at 40° C. for 4 h to obtain a second reaction mixture;
[0052] S3. The second reaction mixture is filtered, the filter cake is washed with pure water for 3 times, and then dried and calcined at a temperature of 500° C. for 8 h to obtain a manganese iron phosphate precursor.
[0053] The above-obtained ferromanganese phosphate precursor was mixed with 2.77 kg of lithium carbonate and ground to a particle size D50 of 0.2-0.4 um. The obtained ground material was spray-dried in a centrifugal sprayer and then calcined at 650°C in a nitrogen furnace for 13 h. After calcination, it was air flow crushed to obtain a lithium ferromanganese phosphate positive electrode material with a particle size D50 of 1.5-2.5 um for standby use.
[0054] The microstructure of the obtained lithium manganese iron phosphate cathode material was observed, and the results are as follows Figure 1 As shown by Figure 1 It can be seen that the positive electrode material is a sheet-like skeleton-loaded carbon-coated lithium manganese iron phosphate.
[0055] Example 2
[0056] A method for preparing a ferromanganese phosphate precursor comprises the following steps:
[0057] S1, adding 1.79 kg of iron powder (particle size ≤ 100 um) into 1 L of 80 mol / L phosphoric acid solution, stirring and reacting at 60° C. for 4 h to obtain a first reaction mixture;
[0058] S2, 5.5 kg manganese carbonate, 44.16 g sodium dodecyl sulfate and 151.3 g UiO-66-NH 2 / Nb 2 CT x The composite material is added to the first reaction mixture, and stirred for reaction at 60° C. for 3 h to obtain a second reaction mixture;
[0059] S3. The second reaction mixture is filtered, and the filter cake is washed with pure water for 4 times. After drying, it is calcined at a temperature of 600° C. for 7 hours to obtain a manganese iron phosphate precursor.
[0060] The above-obtained ferromanganese phosphate precursor was mixed with 2.96 kg of lithium carbonate and ground to a particle size D50 of 0.2-0.4 um. The obtained ground material was spray-dried in a centrifugal sprayer and then calcined at 650°C in a nitrogen furnace for 13 h. After calcination, it was air flow crushed to obtain a lithium ferromanganese phosphate positive electrode material with a particle size D50 of 1.5-2.5 um for standby use.
[0061] Example 3
[0062] A method for preparing a ferromanganese phosphate precursor comprises the following steps:
[0063] S1, adding 2.14 kg of iron powder (particle size ≤ 100 um) into 1 L of 85 mol / L phosphoric acid solution, stirring and reacting at 80° C. for 3 h to obtain a first reaction mixture;
[0064] S2, 6.45Kg manganese carbonate, 64.5g citric acid and 338.4g UiO-66-NH 2 / Nb 2 CT x The composite material is added to the first reaction mixture, and stirred for reaction at 80° C. for 2 h to obtain a second reaction mixture;
[0065] S3. The second reaction mixture is filtered, the filter cake is washed with pure water for 3 times, and then dried and calcined at a temperature of 700° C. for 5 h to obtain a manganese iron phosphate precursor.
[0066] The above-obtained ferromanganese phosphate precursor was mixed with 3.14 kg of lithium carbonate and ground to a particle size D50 of 0.2-0.4 um. The obtained ground material was spray-dried in a centrifugal sprayer and then calcined at 650°C in a nitrogen furnace for 13 h. After calcination, it was air flow crushed to obtain a lithium ferromanganese phosphate positive electrode material with a particle size D50 of 1.5-2.5 um for standby use.
[0067] Comparative Example 1
[0068] A method for preparing a ferromanganese phosphate precursor, compared with Example 1, the UiO-66-NH 2 / Nb 2 CT x The composite material was replaced with the product prepared in Example 1 of the same mass, Nb 2 CT xThe remaining raw materials, parameters and preparation process are the same as those in Example 1.
[0069] Comparative Example 2
[0070] A method for preparing a ferromanganese phosphate precursor, compared with Example 1, the UiO-66-NH 2 / Nb 2 CT x The composite material is replaced with an equal mass of Nb 2 CT x , Nb 2 CT x The remaining raw materials, parameters and preparation process are the same as those in Example 1.
[0071] Comparative Example 3
[0072] A method for preparing a ferromanganese phosphate precursor, compared with Example 1, the UiO-66-NH 2 / Nb 2 CT x The composite material is replaced with UiO-66-NH 2 The remaining raw materials, parameters and preparation process are the same as those in Example 1.
[0073] Comparative Example 4
[0074] A method for preparing a ferromanganese phosphate precursor, compared with Example 1, the method comprises the following steps: 2 / Nb 2 CT x Composite material" was replaced by "54.08 g of UiO-66-NH 2 / Nb 2 CT x The rest of the raw materials, parameters and preparation process are the same as those in Example 1.
[0075] Comparative Example 5
[0076] A method for preparing a ferromanganese phosphate precursor, compared with Example 3, the "338.4 g UiO-66-NH 2 / Nb 2 CT x Composite material" was replaced by "355.3 g UiO-66-NH 2 / Nb 2 CT x The rest of the raw materials, parameters and preparation process are the same as those in Example 1.
[0077] The lithium manganese iron phosphate positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were assembled into button cells for electrochemical performance testing. The assembly process was as follows:
[0078] The lithium iron manganese phosphate positive electrode material, conductive agent, PVDF (polyvinylidene fluoride) and NMP (N-methylpyrrolidone) were mixed evenly in a mass ratio of 90:5:5:100 to obtain a positive electrode slurry, which was coated on an aluminum foil and dried under vacuum to make a positive electrode sheet. The positive electrode sheet, metal lithium sheet, separator and electrolyte were assembled into a button cell for testing. The separator was a polypropylene microporous membrane (Celgard 2300), and the electrolyte was 1 mol / L lithium hexafluorophosphate (ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1);
[0079] Electrochemical performance test:
[0080] At room temperature, the voltage range is 2.5-4.3V, and the battery capacity is tested at 0.1C and 1C rates;
[0081] At room temperature, the voltage range is 2.5-4.3V, and the charge and discharge cycle is repeated 300 times at a rate of 0.1C, and the capacity retention rate after the cycle is tested;
[0082] The results are shown in Table 1:
[0083]
[0084] It can be seen from the data recorded in Table 1 that the discharge specific capacity of the lithium iron phosphate positive electrode material prepared by the precursors described in Examples 1-3 at 0.1C is 159.8-164.6 mAh·g -1, The discharge capacity at 1C is 149.7-152.6 mAh g -1, At a rate of 0.1C, the charge and discharge cycles were repeated 300 times, and the capacity retention rate was ≥98.5%, which was significantly higher than that of comparative examples 1-5, indicating that the lithium iron phosphate positive electrode material prepared from the manganese iron phosphate precursor prepared by the present invention has better electrochemical performance.
[0085] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0086] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a ferromanganese phosphate precursor, characterized in that: The following steps are involved: S1, adding iron powder to phosphoric acid solution, stirring and reacting at 40-80° C. for 3-5 hours to obtain a first reaction mixture; S2, manganese carbonate, surfactant and UiO-66-NH2 / Nb2CT x The composite material is added to the first reaction mixture, and stirred for reaction at 40-80° C. for 2-4 hours to obtain a second reaction mixture; S3, filtering the second reaction mixture, washing the filter cake with pure water for 3-5 times, drying and calcining to obtain a manganese iron phosphate precursor; The molar ratio of manganese in manganese carbonate, iron in iron powder and phosphorus in phosphoric acid solution is 0.55-0.65:0.35-0.45:1-1.05, UiO-66-NH2 / Nb2CT x The amount of the composite material is 0.5-2.0% of the total mass of manganese carbonate, iron powder and phosphoric acid, and the amount of the surfactant is 0.5-1% of the mass of manganese carbonate; The UiO-66-NH2 / Nb2CT x The method for preparing the composite material comprises the following steps: Zirconium chloride and 2-aminoterephthalic acid were added to DMF and stirred until completely dissolved to obtain a mixed solution a. x The mixture a was added to the reactor, and the reaction was carried out at 120 ° C for 24 h under vacuum conditions. After the reaction was completed, it was cooled to room temperature. The reaction product was washed with DMF and anhydrous ethanol for 3-5 times respectively, and freeze-dried to obtain UiO-66-NH2 / Nb2CT x Composite materials.
2. The method for preparing a ferromanganese phosphate precursor according to claim 1, characterized in that: Zirconium chloride, 2-aminoterephthalic acid, DMF and Nb2CT x The dosage ratio is 400mg:248mg:30mL:1.5-3g.
3. The method for preparing a ferromanganese phosphate precursor according to claim 1, characterized in that: The Nb2CT x The preparation method comprises the following steps: Add lithium fluoride to the hydrochloric acid solution, stir for 3-5 minutes, then add Nb2AlC, keep warm at 40-50℃ for 24 hours, after the reaction, wash with dilute hydrochloric acid and ultrapure water 2-3 times respectively, collect the precipitate after washing, and vacuum dry the precipitate to obtain Nb2CT x .
4. The method for preparing a ferromanganese phosphate precursor according to claim 3, characterized in that: The usage ratio of lithium fluoride, hydrochloric acid solution and Nb2AlC is 1.6g:25-30mL:1g, and the concentration of hydrochloric acid solution is 9mol / L.
5. The method for preparing a ferromanganese phosphate precursor according to claim 1, characterized in that: The surfactant is at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and citric acid.
6. The method for preparing a ferromanganese phosphate precursor according to claim 1, characterized in that: The concentration of the phosphoric acid solution is 75-85 mol / L.
7. The method for preparing a ferromanganese phosphate precursor according to claim 1, characterized in that: The calcination temperature is 500-700°C and the time is 5-8h.
8. A ferromanganese phosphate precursor, characterized in that: The method is prepared according to any one of claims 1 to 7.
Citation Information
Patent Citations
Modified lithium iron phosphate material, preparation method and application thereof
CN108199041A
MXene-coated UiO-66-NH2 solvent-free nanofluid, preparation and application thereof, composite material and preparation of MXene-coated UiO-66-NH2 solvent-free nanofluid
CN114753148A